Fungicidal action and structure correlation of monosubstituted phenyl isothiocyanates - Saksena, N K (Folia microbiologica, 1985)
The fungicidal activity of 10 monosubstituted phenyl isothiocyanates was observed with four plant pathogens. The ortho- and meta-substituted derivatives possessed a fair activity while the para-substituted ones proved to be highly fungicidal when compared to the control Agrosan GN.
Keywords: Spores, Fungal; Fungicides, Industrial; spory hub; Alternaria; průmyslové fungicidy; houby; thiokyanatany; Fungi; Isothiocyanates; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Helminthosporium; Fusarium; Thiocyanates; isothiokyanatany